2006
DOI: 10.1016/j.jbiomech.2005.02.014
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging of rapid deformation and strain in an animal model of traumatic brain injury

Abstract: In traumatic brain injury (TBI) rapid deformation of brain tissue leads to axonal injury and cell death. In vivo quantification of such fast deformations is extremely difficult, but important for understanding the mechanisms of degeneration post-trauma and for development of numerical models of injury biomechanics. In this paper, strain fields in the brain of the perinatal rat were estimated from data obtained in vivo during rapid indentation. Tagged magnetic resonance (MR) images were obtained with high spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 26 publications
1
51
0
2
Order By: Relevance
“…The observed injury of the cingulum/external capsule suggests also that a substantial mechanical strain (tissue deformation) is experienced by these tracts. It has been shown that the infant brain may be under larger peak stress magnitude (deforming force per unit area) compared to the mature brain (Levchakov et al, 2006), and indentation of the skull of infant rats at a similar location used in the current study resulted in very high strain and rapid tissue deformation in the cingulum/external capsule (Bayly et al, 2006a). Another contributing factor to axonal vulnerability may be the fact that subcortical white matter tracts in the P7 mouse are still unmyelinated and contain predominantly immature oligodendrocytes (Craig et al, 2003).…”
Section: Discussionmentioning
confidence: 78%
“…The observed injury of the cingulum/external capsule suggests also that a substantial mechanical strain (tissue deformation) is experienced by these tracts. It has been shown that the infant brain may be under larger peak stress magnitude (deforming force per unit area) compared to the mature brain (Levchakov et al, 2006), and indentation of the skull of infant rats at a similar location used in the current study resulted in very high strain and rapid tissue deformation in the cingulum/external capsule (Bayly et al, 2006a). Another contributing factor to axonal vulnerability may be the fact that subcortical white matter tracts in the P7 mouse are still unmyelinated and contain predominantly immature oligodendrocytes (Craig et al, 2003).…”
Section: Discussionmentioning
confidence: 78%
“…[1][2][3][4][5][6][7] Detailed biomechanical and heuristics studies consistently show the vulnerability of WM, particularly the CC and longcoursing fasciculi, especially within frontotemporal regions. [8][9][10][11][12] DTI abnormalities within the CC in patients with TBI have been well documented in both the acute and chronic phase of injury. [13][14][15][16][17][18] Because of the ease with which the CC can be delineated by MR imaging as a region of interest along with being the largest commissural fiber tract in the brain, the CC is also the most widely investigated WM brain structure in TBI.…”
Section: ϫ3mentioning
confidence: 99%
“…The transverse, or shear, displacement component describes volume-conserving deformation. The transverse displacement is governed by (4) If the motion is harmonic with excitation frequency ω (5) Equation (4) can then be solved for μ, yielding (6) We note in passing that estimates of shear modulus can be made directly from phase measurements, without conversion to units of displacement. Since the displacement is simply proportional to phase, , the previous equation can be written as…”
Section: Shear Waves In Elastic Materialsmentioning
confidence: 99%
“…The mechanical properties of brain tissue govern how it deforms during an impact or high acceleration. The strain imposed on the brain during TBI has been of interest to researchers for more than sixty years, and methods for accurately measuring the strain field in the brain during acceleration continue to be developed [4,5]. Margulies [6] developed an empirical correlation between critical shear strain and the onset of diffuse axonal injury (DAI) in response to rotational inertial loading of the brain.…”
Section: Introductionmentioning
confidence: 99%